Arenediazonium Tosylates in Synthesis of 1,3,5-Substituted Formazans; Current topics in Organic Chemistry - Petunin P. V. Pavel Vasilievich; Postnikov P. S. Pavel Sergeevich; Trusova M. E. Marina Evgenievna; Mostovich E. A. Evgenii Alexeevich (2015, 2015)
Title screen